Surfactant science and technology : retrospects and prospects - Romsted, Laurence, S. (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
'A celebration was held at the 18th Surfactants in Solution (SIS) meeting in November 2010 in Melbourne in honor of Kashmiri Mittal's 100th edited book. Those who participated in the symposium are leaders in the fields of surfactant-based, physical, organic, and materials chemistries, and many agreed to contribute a chapter to this book. Some chapters are contributed by others who wanted to participate in the meeting but were unable to attend. The authors were asked to give an overview of their research area and to include sections on past, present, and future directions. The authors updated and revised their manuscripts as needed in 2012. The cumulative result is a broad perspective on the current developments in and future of surfactant science and technology. The next SIS will be held in Coimbra, Portugal, in June 2014, the 20th biennial meeting over about two score years. During this time, the field of surfactant chemistry has expanded dramatically and has evolved considerably, aided by the development of modern instrumentation and new experimental techniques that permit exploration of surfactant properties in both the bulk and at molecular levels and by simulation. The physical properties of surface-active agents, commonly known as surfactants, amphiphiles, detergents, or soaps, are governed by covalently bonding two opposite chemical properties in one molecule: a water-insoluble hydrophobic tail, typically composed of linear hydrocarbon chemically bonded to polar or ionic headgroup and counterion. These surfactant monomers or unimers self-assemble into a plethora of aggregate structures such as micelles, microemulsions, vesicles, and emulsions depending on solution composition, but they also form surfactant monolayers at the air, liquid, and solid interface'--
Part 1. Theory of self-assembly and ion-specific effects -- part 2. Surfactants at solid-liquid interfaces -- part 3. Polymeric surfactants and polymer/surfactant mixtures -- part 4. Biosurfactants -- part 5. Formulation and application of surfactant aggregates -- part 6. Formulation and application of emulsions.
'A Festschrift in honor of Dr. Kash Mittal'--Title page.
'Written by the stars of surface and colloid chemistry, this edited work covers developments in the field of association colloid chemistry. The book presents an overview of the direction of the field and gives insight into the forces controlling surfactant and polymer self-assembly. The text addresses numerous research areas, including rheology, surfactant ionic liquids, foams, forces responsible for structural changes of micelles, polymeric surfactants, phase separation, surfactant interactions with solid surfaces, protein and enzymesurfactant interactions, solubilization, mesophases in concentrated solutions, enhanced oil recovery, surfactants for liquid CO2, and biobased surfactants'-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Surfact chemistry; Surface active agents; Colloids